2019
DOI: 10.1021/acschemneuro.9b00166
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Peripheral Neuropathic Pain by the Small-Molecule Natural Product Physalin F via Block of CaV2.3 (R-Type) and CaV2.2 (N-Type) Voltage-Gated Calcium Channels

Abstract: No universally efficacious therapy exists for chronic pain, a disease affecting one-fifth of the global population. An overreliance on the prescription of opioids for chronic pain despite their poor ability to improve function has led to a national opioid crisis. In 2018, the NIH launched a Helping to End Addiction Long-term plan to spur discovery and validation of novel targets and mechanisms to develop alternative nonaddictive treatment options. Phytochemicals with medicinal properties have long been used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 78 publications
(137 reference statements)
1
22
0
Order By: Relevance
“…Thus, betulinic acid may represent a promising alternative to treat taxane‐related peripheral neuropathy, without causing tolerance (Bellampalli et al, 2019). In a continuous effort to identify new analgesic drugs lacking abuse potential, Shan et al (2019) demonstrated that the small molecule physalin F, isolated from Physalis acutifolia , prevents paclitaxel‐induced tactile allodynia in rats when dosed intrathecally. The same study indicated that physalin F promotes analgesia by blocking R‐ and N‐type Ca v channels and excitatory postsynaptic currents, without any interaction with opioid receptors (Shan et al, 2019).…”
Section: Taxane‐induced Peripheral Neuropathymentioning
confidence: 99%
“…Thus, betulinic acid may represent a promising alternative to treat taxane‐related peripheral neuropathy, without causing tolerance (Bellampalli et al, 2019). In a continuous effort to identify new analgesic drugs lacking abuse potential, Shan et al (2019) demonstrated that the small molecule physalin F, isolated from Physalis acutifolia , prevents paclitaxel‐induced tactile allodynia in rats when dosed intrathecally. The same study indicated that physalin F promotes analgesia by blocking R‐ and N‐type Ca v channels and excitatory postsynaptic currents, without any interaction with opioid receptors (Shan et al, 2019).…”
Section: Taxane‐induced Peripheral Neuropathymentioning
confidence: 99%
“…The changes in [Ca 2+ ]c changes were examined with a ratio of F340/ F380, calculated after subtracting background from both channels. Recordings of total calcium currents were obtained using recording solutions and protocols (also illustrated in the figures) described earlier [18]. The internal solution consisted of (in mM): 150 CsCl 2 , 10 HEPES, 5 Mg-ATP, and 5 BAPTA (pH 7.3, mOsm/L = 290-310) and external solution contained (in mM): 110 NMDG, 10 BaCl 2 , 30 TEA-Cl, 10 HEPES, 10 glucose and 10 μM HEPES (pH 7.3, mosM/L = 310-315).…”
Section: Calcium Imaging In Acutely Dissociated Rat Dorsal Root Ganglmentioning
confidence: 99%
“…The internal solution consisted of (in mM): 150 CsCl 2 , 10 HEPES, 5 Mg-ATP, and 5 BAPTA (pH 7.3, mOsm/L = 290-310) and external solution contained (in mM): 110 NMDG, 10 BaCl 2 , 30 TEA-Cl, 10 HEPES, 10 glucose and 10 μM HEPES (pH 7.3, mosM/L = 310-315). The neurons were subjected to current−density (I − V) and activation/inactivation voltage protocols as previously described and shown in the figures [18].…”
Section: Calcium Imaging In Acutely Dissociated Rat Dorsal Root Ganglmentioning
confidence: 99%
See 2 more Smart Citations